JEULAMEE ON ACEH PEOPLE’S MARRIAGE IN ISLAMIC LAW AND PHENOMENOLOGY PERSPECTIVE - Muhammad Zainuddin; Roibin Roibin; Abbas Arfan (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2022)
Jeulamee was the nickname of dowry in Aceh, it was just that the term jeulamee had an exclusive meaning, that gold ‎is the only form of dowry that was traditionally recognized in Aceh. Another uniqueness was that gold was ‎measured by the size of the mayam. One mayam alone was equivalent to 3. 3 grams of gold. Jeulamee was a hot issue that repeatedly stuck out along with the holding of marriages in the community. When ‎it was heard that a marriage was about to took placed, the opinion of the jeulamee would followed him. The ‎screams of the youth in Aceh, “hana peng hana inong” (no money, no wife) seemed to voiced a cynical criticism ‎that only men with the title of financial freedom could marry. This studied aims to explained and analyze the ‎concept of jeulamee in Acehnese marriage from the perspective of Islamic Law. The typed of researched used was sociological legal researched, with a phenomenological approached and the data ‎analysis was descriptive-qualitative. Data was collected by used interview and observation techniques. The ‎results showed that the obligation of gold as a marriage dowry in Peunaron sub-district did not conflict with ‎Islamic Law, this was evidenced by the absence of the opinion of the four madhhab scholars who oblige and ‎forbid it, there was even a hadith of the prophet Muhammad SAW that allowed his companions to marry with a gold dowry. There were two arguments for the preservation of jeulamee, namely: first, materialistic idealist, that jeulamee was ‎a tradition that was created and had a good purpose, such as preventing divorce, motivating young people who ‎want to got married to worked hard, because wealth was a necessary provision to navigate life, and uplift and ‎glorify women; second, normative formalistic, that jeulamee was a law of agreement from the community ‎‎(becoming customary law) and did not deviate from the concept of dowry in Islam.